A Cross-Sectional Observational Study of Pneumococcal Carriage in Children, Their Parents, and Older Adults Following the Introduction of the 7-Valent Pneumococcal Conjugate Vaccine. Issue 1 (January 2015) - Hamaluba, Mainga; Kandasamy, Rama; Ndimah, Susan; Morton, Richard; Caccamo, Marisa; Robinson, Hannah; Kelly, Sarah; Field, Aimee; Norman, Lily; Plested, Emma; Thompson, Ben A.V.; Zafar, Azhar; et al.
<x xml:space="preserve">Abstract</x> Abstract Using nasopharyngeal carriage as a marker of vaccine impact, pneumococcal colonization and its relation to invasive disease were examined in children, their parents, and older adults in the United Kingdom following introduction of 7-valent pneumococcal conjugate vaccine (PCV7) and prior to 13-valent pneumococcal conjugate vaccine (PCV13). A cross-sectional observational study was conducted, collecting nasopharyngeal swabs from children aged 25 to 55 months who had previously received 3 doses of PCV7, their parents, and adults aged ≥65 years. Pneumococcal serotyping was conducted according to World Health Organization guidelines with nontypeable isolates further analyzed by molecular serotyping. A national invasive disease surveillance program was conducted throughout the corresponding period. Pneumococcus was isolated from 47% of children, 9% of parents, and 2.2% of older adults. For these groups, the percentage of serotypes covered by PCV7 were 1.5%, 0.0%, and 15.4%, with a further 20.1%, 44.4%, and 7.7% coverage added by those in PCV13. In each group, the percentage of disease due to serotypes covered by PCV7 were 1.0%, 7.4% and 5.1% with a further 65.3%, 42.1%, and 61.4% attributed to those in PCV13. The prevalence of carriage is the highest in children, with direct vaccine impact exemplified by low carriage and disease prevalence of PCV7 serotypes in vaccinated children, whereas the indirect effects of herd protection are implied by similar observations in unvaccinated parents and older adults.